2012
DOI: 10.3109/02652048.2012.686526
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterisation of doxorubicin-releasing chitosan microspheres for anti-cancer chemoembolisation

Abstract: The aims of this study were to design and characterise doxorubicin-loaded chitosan microspheres for anti-cancer chemoembolisation. Doxorubicin-loaded chitosan microspheres were prepared by emulsification and cross-linking methods. Doxorubicin-chitosan solution was initially complexed with tripolyphosphate (TPP) to improve drug loading capabilities. Doxorubicin-loaded chitosan microspheres were highly spherical and had approximately diameters of 130-160 µm in size. Drug loading amount and loading efficiency wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Its biodegradation products are harmless amino sugars that can be absorbed by the body (Hejazi, Amiji, 2003). Chitosan is widely used to prepare particular drug delivery systems such as microparticules (Yuan, Chessnut, Utturkar, 2007;Ma, Liu, 2010;Park, Lee, Lee, 2012;Caetano, Almeida, Gonçalves, 2016;Gadalla et al, 2016;Jeon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its biodegradation products are harmless amino sugars that can be absorbed by the body (Hejazi, Amiji, 2003). Chitosan is widely used to prepare particular drug delivery systems such as microparticules (Yuan, Chessnut, Utturkar, 2007;Ma, Liu, 2010;Park, Lee, Lee, 2012;Caetano, Almeida, Gonçalves, 2016;Gadalla et al, 2016;Jeon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microspheres of chitosan cross-linked with polyethylene glycol were prepared by emulsion cross-linking and found to slow the release of 5-fluorouracil up to 24hr to colonic region and increased its anticancer activity [17]. Furthermore, various formulations of chitosan-based models loaded with doxorubicin and cisplatin were prepared and evaluated, and the results demonstrated promising features for these newly developed formulations to improve efficacy and safety of these cytotoxic agents [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The cytocompatibility studies in HepG2 (liver hepatocellular carcinoma) cells demonstrated that viability of the HepG2 cells was near 100 % (96.57−104.70 %) at the tested concentrations (0 −100 μg/mL) after 48 h of incubation, indicating that hollow microspheres have excellent nontoxicity toward HepG2 cells. Park et al designed doxorubicin-loaded chitosan microspheres by emulsification and crosslinking methods [75]. In vivo study demonstrated blank chitosan microspheres led to a reduction in the tumour size; the size decreased by approximately 25 % and in case of doxorubicin-loaded chitosan microspheres tumour sizes were shrunk to one-third of the initial size.…”
Section: Microspheresmentioning
confidence: 99%